Sense of frustration: The debate on land reform in South Africa - Melanie Müller; Laura Kotzur (Stiftung Wissenschaft und Politik (SWP), 2019)
In December 2018, the ruling African National Congress (ANC) and opposition party, Economic Freedom Fighters (EFF), passed an amendment to the constitution in the South African Parliament. It was intended to give concrete form to existing options to expropriate land without compensation. The narrative of land reform discussions in South Africa often creates the impression that the expropriation of land owned by white farmers without compensation could solve the country's problem of unequal income distribution. It would, however, take a whole set of political reforms to create more social justice. Visible successes might help appease those groups that are disappointed with South African democracy 25 years after the end of apartheid, but if the reforms fail then this will likely exacerbate the already palpable sense of frustration felt by ordinary South Africans.
Keywords: 320